Understanding Brain Plasticity in Learning Process - Yuliana, Yuliana (International Journal of Research in STEM Education, 2020)
Brain plasticity takes an essential part in the learning process and memory retaining. Brain plasticity is connected with myelin sheath development and oligodendrocyte plasticity. Dynamic myelination is attained through certain learning activities. Oligodendrocyte plasticity means changes of oligodendrocyte precursor cell number either increasing or decreasing. This review aims to reveal what learning style is better in optimizing learning capacity by understanding dynamic myelination, brain plasticity, oligodendrocyte plasticity, and learning process. The review paper was based on journal reading. Keywords for literature searching are "Learning, myelin, brain, plasticity, oligodendrocyte" with filters in the last 5 years in the PubMed website. Pubmed was considered as one of the qualified journals. It doesn't rule out the possibility of using another journal that is not listed in PubMed. Result showed 36 articles. Other citations were added based on the previously selected journals. The learning process is closely related to encoding. Making schema while learning new objects are very useful in increasing oligodendrocytes cells number. The paper limitation is it didn't describe how the learning process might improve school performance and success in later life. There isn't any comparison about how each learning activity has an unequal effect on dynamic myelination, brain plasticity, and daily life skills improvement. This review paper's significance is myelin was not static, but it is dynamically changed through learning activities, new experiences, musical, or even practical training. Exposure to a new environment in the learning process will improve myelination and optimize learning. Learning new things is good for our brain because it will prevent dementia.